KRITIKAL ANALISIS PENEGAKAN HUKUM TERHADAP TINDAK PIDANA CYBER PORNOGRAPHY: KAJIAN PERBANDINGAN HUKUM NEGARA INDONESIA DAN CHINA - Eko Nurisman,; Emiliya Febriyani,; Suwandi, (JIL : Journal of Indonesian Law, 2023)
The rise of cyber pornography is a crucial problem that attacks the morals of the young generation in various countries. Every country in the world has different regulations in handling cyber pornography crime as a form of prevention. Indonesia until now still has difficulties in suppressing the high crime of cyber pornography, therefore good regulation and law enforcement are needed to suppress the high cyber pornography. Reflecting on China which has proven and succeeded in suppressing the high crime of cyber pornography. By using the legislative approach and comparative approach, this research proves that by conducting a comparative study of law with other countries, namely China, it can be an alternative to national law reform, especially in dealing with the rise of cyber pornography in Indonesia.